COMPARISON OF AXILLARY DRAIN OUT PUT IN CONVENTIONAL AND ADVANCEDCOMPRESSIVE ENERGY SOURCE LIKE ULTRASONIC SCALPEL AND LIGASURE DISSECTION OF AXILLA IN BREAST CANCER SURGERY - Zafar, Shaista; Khan, Mumtaz Ahmad; Rafiq, Umber; Mahmood, Namrah (Journal of Ayub Medical College Abbottabad, 2021)
Background: Breast cancer is the most common malignancy worldwide. Surgical treatment of axilla is a part of treatment of locally advanced breast cancer. Conventional knot tying plus electrocautery and advanced compressive energy sources are used to reduce the continued axillary serous fluid discharge when drains are in place and seroma formation afterwards. Methods: This double-blind comparative study was carried out between April 2018 to October 2019. In total 180 patients undergoing axillary dissection for treatment of locally advanced breast cancer were recruited. Patients were divided into two groups (C and H) depending upon method of dissection used for axillary surgery. Results: For most participants, amount of axillary drain volume in Group C was between 400-700ml (in 48.9% participants) and for Group H more than 700 ml (in 44.4% participants). This difference is not statistically significant (p=0.288). Duration of hospital stay (p=0.003) and duration of drain placement was significantly longer (p=0.019) for most participants in Group H. More hospital visits were required for the said group. There was statistically significant co-relation between immediate complications and haemostasis techniques (p=0.003) with more incidence of Seroma noticed in Group H than in Group C. Conclusion: Current study shows limited benefits of using ultrasonic scalpels in breast cancer surgeries. Variables such as BMI, Age and chemotherapy need to be controlled in order to derive a true comparison.